2016
DOI: 10.7150/jca.15181
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Regulatory Volume Decrease Enhances the Cytocidal Effect of Hypotonic Shock in Hepatocellular Carcinoma

Abstract: Background: Hypotonic shock induces cytocidal effects through cell rupture, and cancer therapy based on this mechanism has been clinically administered to hepatocellular carcinoma patients. We herein investigated the effectiveness of hypotonic shock combined with the inhibition of regulatory volume decrease as cancer therapy for hepatocellular carcinoma.Methods: Morphological changes in human hepatocellular carcinoma cell lines were observed under a differential interference contrast microscope connected to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Bodily and cellular functions are controlled by various factors including ions such as Na + , K + , Ca 2+ , Mg 2+ , Zn 2+ , and Cl − [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. On the one hand, pH (−log[H + ]) is recognized as one of classical items considered to be already fully understood in roles and mechanisms of homeostasis.…”
Section: Variety Of the Interstitial Fluid Phmentioning
confidence: 99%
“…Bodily and cellular functions are controlled by various factors including ions such as Na + , K + , Ca 2+ , Mg 2+ , Zn 2+ , and Cl − [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. On the one hand, pH (−log[H + ]) is recognized as one of classical items considered to be already fully understood in roles and mechanisms of homeostasis.…”
Section: Variety Of the Interstitial Fluid Phmentioning
confidence: 99%
“…Several in vitro and in vivo studies have investigated the cytocidal effects of hypotonic stress on cancer cells (6)(7)(8)(9). We examined the changes in the morphology and volume of cancer cells subjected to hypotonic shock using several methods, such as a differential interference contrast microscope connected to a digital video camera, and revealed that DW exposure rapidly increases cell volume followed by cell rupture in esophageal, gastric, colonic, pancreatic and liver cancer cell lines (12)(13)(14)(15)(16). Our research group also determined the therapeutic effects of a peritoneal injection of DW into nude mice for the treatment of peritoneal dissemination of GC (21).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of cell volume changes in GC cells after hypotonic shock using a high-resolution flow cytometer. Cell volume measurements were performed using a high-resolution flow cytometer (Cell Lab Quanta; Beckman Coulter, Inc.), as previously described (12)(13)(14)(15)(16). This flow cytometer was designed to measure the electronic volume (EV) of a cell, and EV data of >10,000 cells were collected and analyzed using Quanta control software (Beckman Coulter, Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells are assumed to be approximately spherical; their diameters d or cross‐sectional areas are estimated and used to calculate the volume as ⅙πd 3 . Imaging is usually done in transmitted light but fluorescence can also be used . It is obvious that representing even a loosely attached cell with a sphere (rather than a spheroid or some other shape) requires a certain leap of faith from the experimenter, and direct testing of cell sphericity is rarely done .…”
Section: Geometrical Approachesmentioning
confidence: 99%